Classification of Players Across the Australian Rules Football Participation Pathway Based on Physical Characteristics. Issue 3 (12th March 2022) - Haycraft, Jade A.Z.; Kovalchik, Stephanie; Pyne, David B.; Robertson, Sam
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Haycraft, JAZ, Kovalchik, S, Pyne, DB, and Robertson, S. Classification of players across the Australian Rules football participation pathway based on physical characteristics. J Strength Cond Res 36(3): 702–709, 2022—This study investigated the utility of physical fitness and movement ability tests to differentiate and classify players into Australian Football League (AFL) participation pathway levels. Players ( n = 293, age 10.9–19.1 years) completed the following tests; 5-m, 10-m, and 20-m sprint, AFL planned agility, vertical jump (VJ), running VJ, 20-m multistage fitness test (MSFT), and athletic ability assessment. A multivariate analysis of variance between AFL participation pathway levels was conducted, and a classification tree determined the extent to which players could be allocated to relevant levels. The magnitude of differences between physical fitness and movement ability were level-dependent, with the largest standardized effect size (ES) between Local U12, Local U14, and older levels for most physical fitness tests (ES: −4.64 to 5.02), except the 5-m and 10-m sprint. The 20-m, 5-m, AFL agility, 20-m MSFT, overhead squat, and running VJ (right) contributed to the classification model, with 57% overall accuracy reported (43% under cross-validation). National U16 players were easiest to classify (87%), while National U18 players were most difficult (0%). Physical fitness tests do not seem to differentiate between players after selection into AFL talent pathway levels. Other attributes (i.e., skill, psychological, and sociocultural) should be prioritized over physical fitness and movement attributes by selectors/coaches when considering selection of talented players.